Quality of life and housing policy. neighborhood improvement programs in cordoba, argentina. case study malvinas argentinas neighborhood (2010)
In this article we analyze the assumptions about quality of life that guide the Program of Neighborhood Improvement –Promeba– implemented in the local arena, and we reflect on the extent to which they have had a positive impact on the quality of life of the targeted families. The empirical research is based on the case study: Malvinas Argentinas neighborhood (located in Córdoba metropolitan area, in Argentina). The methodology considered triangulation in data collection. The double articulation the information crossed –written and compiled from reviews of the different actors involved– allowed us to understand the assumptions behind the housing policy implemented and also its performance.